Inflammatory bowel diseases and primary immunodeficiency diseases. Issue 4 (2nd October 2018) - Kanegane, Hirokazu
Abstract: Recent advances in molecular biology have provided important insights into the genetic background of various inflammatory diseases. In particular, genome-wide association studies of inflammatory diseases have revealed genetic loci that play critical roles in the pathology of inflammation. Whole-exome and whole-genome sequencing analyses have also identified more than 300 causative genes for primary immunodeficiency diseases (PIDs). Some genetic loci that are associated with inflammatory diseases are mutated in PIDs, suggesting close relationships between inflammation and PIDs. Inflammatory diseases for which genetic associations have been described include inflammatory bowel disease (IBD), multiple sclerosis, rheumatoid arthritis, type 1 diabetes mellitus, and systemic lupus erythematosus. Herein, I discuss about the genetic interactions between IBD and PIDs.